2020
DOI: 10.1109/access.2020.2999851
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Driver Model to Predict Driver Control at Unsignalised Intersections

Abstract: The number of cyclists fatally struck when crossing a driver's travel path at an unsignalised intersection has been stable in recent years, indicating that more effort should be made to improve safety in this specific conflict scenario. The most recent safety systems help drivers avoid collisions with cyclists, but improving cyclist safety further requires resolving challenges unique to bicycles and cyclists. In this paper we propose a predictive computational model of driver behaviour in the intersection scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…As mentioned in the introduction, most evidence accumulation modeling work in the literature focuses on abstract tasks of perceptual discrimination or value-based choice. Our results instead add to a more limited (but growing) body of support for drift diffusion type models in locomotion and general sensorimotor interaction with the world [2,24,31,41,39,48,71,73]. In this type of context, decisions are less purely "perceptual"or "cognitive", and instead arguably more embodied in nature, yet interestingly the same type of decision mechanisms seem to apply.…”
Section: Implications For Wider Computational Modeling Of Cognition and Behaviorsupporting
confidence: 49%
See 1 more Smart Citation
“…As mentioned in the introduction, most evidence accumulation modeling work in the literature focuses on abstract tasks of perceptual discrimination or value-based choice. Our results instead add to a more limited (but growing) body of support for drift diffusion type models in locomotion and general sensorimotor interaction with the world [2,24,31,41,39,48,71,73]. In this type of context, decisions are less purely "perceptual"or "cognitive", and instead arguably more embodied in nature, yet interestingly the same type of decision mechanisms seem to apply.…”
Section: Implications For Wider Computational Modeling Of Cognition and Behaviorsupporting
confidence: 49%
“…We and others have investigated the application of drift diffusion-type models in the road traffic context, with promising results initially for low-level locomotion decisions on applying braking or steering control [39,48,71], more recently also extending to multi-agent interaction situations [2,24,31,41,73].…”
Section: Introductionmentioning
confidence: 99%
“…Third, we show that established evidence accumulation models of decision-making can be extended beyond typical laboratory paradigms with static or intermittently changing abstract stimuli, to a task with clear real-world relevance, and continuously time-varying sensory evidence. We and others have reported that evidence accumulation models show promise for modelling decisions in real-world tasks, e.g., when to apply brakes in response to a developing collision threat [52], [53], [61], or on whether and when to cross a road with oncoming traffic [62], [63]. However, in these types of naturalistic tasks it has not been possible to fit full response time probability distributions per participant, a minimum expectation in evidence accumulation modelling of more typical, abstract laboratory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…However, computational modelling of evidence accumulation decision-making has so far focused on laboratory paradigms using stimuli that (i) have stationary or only intermittently and/or noisily changing saliency over time [46]- [49], and (ii) are abstract in nature, not mapping directly to any real-world task. We and others have begun exploring the applicability of evidence accumulation models in more naturalistic tasks, particularly in vehicle driving [50]- [53], but so far a conclusive test of these models in such contexts has been lacking: Model fitting is rendered more challenging both because real-world sensory evidence tends to be continuously time-varying, which precludes analytical expression of model likelihood functions, and because of difficulties in obtaining sufficient numbers of repeated trials in ecologically relevant experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Future work may investigate the benefit of Bayesian models to provide richer and arguably more valid information about the driver's uncertainty [58], [59], and biologically inspired models [60]- [62]. Once larger data sets of cyclist-overtaking maneuvers become available, more complex machine learning methods based on neural networks or Markov processes may become feasible alternatives to improve predictive accuracy.…”
Section: Future Workmentioning
confidence: 99%